Factors affecting propolis production. Issue 1 (1st January 2023) - Mountford-McAuley, Ruby; Prior, Jason; Clavijo McCormick, Andrea
Abstract : As interest in propolis as a human medicinal product increases, so too does interest in its botanical sources and production. While literature reviewing the chemical constituents and therapeutic properties of propolis is relatively thorough, work regarding the biological, ecological, and environmental factors affecting propolis production is rarer. In this review, literature investigating factors that affect propolis production was compiled with the aim of informing producers on how to improve propolis quality and quantity; and researchers on the knowledge gaps to guide future studies. We identified six factors as being determinants to propolis production: the botanical origin of the resin, honey bee genetics, hive structure, food availability, environmental factors, and disease. This article advocates the importance of future research into these and other factors that affect propolis production.